NT-proBNP and prognostics variables in acute myocardial infarction - Jorge Vendrell Cabrera; Liz Álvarez González; Orlando Álvarez Toledo (ECIMED, 2012)
Introduction An observational descriptive study of traverse court was carried out, in which 70 patients with the definitive diagnosis of acute myocardialinfarction, admitted in the Coronary Care Units from Hermanos Ameijeiras Hospital, were studied. In a period comprehending from January2008 until April 2010.Objective To evaluate the relationship of the fragment amino-terminal of the brain natriuretic peptide (NT-proBNP), with other variables of prognosticutility.Method The data were processed with the statistical software SPSSPC in its version 11.5; the Pearson correlation coefficient was used to evaluatethe relationship between two variables, considering statistical significance the values of p≤ 0,05.Results High levels of NT-proBNP were detected in acute myocardial infarction that were associated to mortality and the occurrence of heart failure(p=0,0001); The relationship with left ventricle ejection fraction was inversely proportional and statistically significant (r=0,425)(p=0,0001),a direct correlation existed with the extension of the ischemic damage estimated by transthoracic echocardiography (r=0,422) (p=0,0001)and with the circulating levels of T Troponin (r=0,514), (p=0,0001). The correlation with the variables that quantify the left ventricle fillingpressure was smaller (r=0,292) (p=0,014).Conclusions Our investigation allowed us to know that levels of NT-proBNP are associated with well-known prognostic variables and they could beinguseful in risk stratification of the patients with the diagnosis of acute myocardial infarction.